PERKAWINAN MASYARAKAT SAMIN DALAM PANDANGAN HUKUM NEGARA - Moh Rosyid (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
Marriage is a demographic matter which needs involvement of state, it deals with registration of marriage contract in order to get legitimation of law. Registration is an evidence of residence’s obedient toward state law (law No.23/2006 about demographic administration, law no.12/200about citizenship). However, in Samin’s community,marriage does not involved a state but based on the ancestors’ teaching and Samin’s principle of life.This study based on a grounded, ethnographic and phenomenologicalresearch, this can be categorized as a social-cultural research.Object of this study is phenomena of social and cultural of Samin’s community in Kudus, specifically on marriage based on adat. This study aims to know a practice of Samin’s marriage in Kudus, steps of marriage including nyumuk, ngendek,nyuwito, penyeksen, and tingkep. Such steps do not involve state’s roles even inmarriage contract.